Yield and economic performance of maize–sweetpotato–bean rotation in a midland agro-ecology of Embu, Kenya - Agili, S.; Njagi, I.; Munda, E.; Kagete, E.; Amboga, S.; Wanyoike, T.; Njoroge, P.; Kibuti, L.; Nyaguthie, M.; Muriithi, G. (2025)
This study evaluates the yield and economic performance of maize–sweetpotato–bean rotations compared with monocropping systems in the midland agro-ecologies of Embu County, Kenya. Results show that crop rotation, particularly sweetpotato–maize rotation, significantly increases marketable yield, profitability, and system resilience while improving soil health and reducing production risks. The findings demonstrate that diversified crop rotations are a viable regenerative agriculture strategy to enhance food security, farm incomes, and climate resilience for smallholder farmers.